Successful rescue of a rare case of refractory shock due to multidrug toxicity: a case report - Xie, Yuhua; Zhou, Yujie; Cao, Yunxing (Frontiers in Pharmacology, 2025)
IntroductionThis article reports the successful treatment experience of refractory shock, acidosis, hypoglycemia, and multi-organ failure after overdose of reserpine, enalapril, and metformin, and aims to provide a reference for the rescue of patients with such poisoning.MethodsA 58-year-old woman with sudden disturbance of consciousness, intractable shock, severe metabolic acidosis, hypoglycemia, and multiple organ dysfunction was urgently transferred to the ICU. The blood pressure could not be maintained after massive rehydration and a large dose of vasoactive drugs. The treatment plan was adjusted quickly after the diagnosis and treatment of medicine, nephrology, cardiology, respiratory, and other disciplines, such as high-dose vasoactive drugs, pressors, continuous blood purification, plasma exchange and hemoperfusion. RESULTS: The dose of vasoactive drugs began to decrease after entering the ICU at 36 h, and the acidosis gradually improved after 46 h. After 72 h, the patient was conscious and was transferred to the general ward on the 9th day.ConclusionThe treatment of mixed drug poisoning involving reserpine, metformin, and enalapril is very challenging. When resuscitating patients with refractory shock caused by such poisoning, early supportive therapies should be started, including gastric lavage, cathartic use, acid correction, improved ventilation, blood purification, and hemodialysis when needed. Additionally, vasoactive drugs may be given without an upper dose limit, as long as side effects are carefully monitored.